(untitled) (The Review of Diabetic Studies, 2025)
Objective: This study was focused on determining Physicians’ perspectives on Stress-Peptic Ulcer Disease prevention and assessing their understanding of SUP guidelines in KSA. Methods: This descriptive cross-sectional study assessed Physician’s knowledge about Stress Peptic Ulcer Disease prevention at King Abdullah Hospital (KAH). The study involved physicians and interns at KAH in Bisha City. The data was collected using an electronic questionnaire through text messages or phone calls. Both data entry and statistical analyses were performed using SPSS. The appropriate statistical tests were used and considered statistically significant at P<0.05. Results: A total of 96 physicians and interns participated in the study, providing valuable insights into their understanding and knowledge of preventing Stress Peptic Ulcer Disease (SPUD). Female physicians were significantly more likely to use SUP than male physicians (p = 0.035, 95% confidence interval for the odds ratio: 0.007 to 0.831). Qualitative data provided valuable insights into physicians’ understanding and knowledge of SPUD prevention, highlighting areas of strength and potential areas for improvement or intervention. It underscores the importance of ongoing education and training to ensure healthcare professionals are equipped with accurate and up-to-date information on SPUD prevention strategies. Conclusion: Proton pump inhibitors are the most widely used preventive measure, and patients are frequently kept on acid suppression therapy even after being released from the hospital. However, medical professionals need more education and awareness about SUP guidelines and proper prescribing practices.